H(x)=x(-2x-4)

Simple and best practice solution for H(x)=x(-2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for H(x)=x(-2x-4) equation:



(H)=H(-2H-4)
We move all terms to the left:
(H)-(H(-2H-4))=0
We calculate terms in parentheses: -(H(-2H-4)), so:
H(-2H-4)
We multiply parentheses
-2H^2-4H
Back to the equation:
-(-2H^2-4H)
We get rid of parentheses
2H^2+4H+H=0
We add all the numbers together, and all the variables
2H^2+5H=0
a = 2; b = 5; c = 0;
Δ = b2-4ac
Δ = 52-4·2·0
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$H_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$H_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$H_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-5}{2*2}=\frac{-10}{4} =-2+1/2 $
$H_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+5}{2*2}=\frac{0}{4} =0 $

See similar equations:

| j-556=-408 | | 13r=-273 | | 19=t/24 | | z/8=14 | | 46=u+-40 | | 44=-4g | | z-(-14)=99 | | 2x-15=x+22 | | 7q=-84 | | -3f=90 | | -92/5m=7 | | x/2.5x=10 | | -12y-6(16Y-16)=1500 | | -2+k=4 | | 1-(2x-1)=2-3x | | 4.9t^2-8t-13=0 | | (3x+2)-15=15-(2x-2) | | 15x=-32 | | 5=c+-14 | | 6g-(-5+4g)=9 | | s+1=4 | | 4(2y+3)=-38 | | .60×p-32=p | | X-67=y+37 | | 2p^2=8 | | 4(y-4)=23 | | 13x+4=12x-14 | | -6x-7(-4x+2)=96 | | y=300(1+.08)5 | | -3x+3(3x+9)=-33 | | 0.2x-3.2=-3÷5=1.8 | | y=12,000(1+.06)4 |

Equations solver categories